2022
DOI: 10.1038/s41598-022-22316-8
|View full text |Cite
|
Sign up to set email alerts
|

Network biology analysis of P23H rhodopsin interactome identifies protein and mRNA quality control mechanisms

Abstract: Rhodopsin is essential for phototransduction, and many rhodopsin mutations cause heritable retinal degenerations. The P23H rhodopsin variant generates a misfolded rhodopsin protein that photoreceptors quickly target for degradation by mechanisms that are incompletely understood. To gain insight into how P23H rhodopsin is removed from rods, we used mass spectrometry to identify protein interaction partners of P23H rhodopsin immunopurified from RhoP23H/P23H mice and compared them with protein interaction partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(124 reference statements)
0
0
0
Order By: Relevance
“…Regardless of these differences, we can still look to models of P23H rhodopsin for future investigation. It is possible that cones regulate expression of misfolded cone opsin through similar pathways as rods regulate P23H rhodopsin, with previous studies demonstrating that Rho P23H mRNA is degraded through mRNA decay and ribosome quality control, while translated P23H rhodopsin is degraded through ER-associated degradation (36,46). Another possibility is that mutant mRNA is subjected to miRNA-mediated decay, as previous studies have shown that miRNAs play a crucial role in photoreceptor homeostasis, function, and survival (47).…”
Section: Discussionmentioning
confidence: 97%
“…Regardless of these differences, we can still look to models of P23H rhodopsin for future investigation. It is possible that cones regulate expression of misfolded cone opsin through similar pathways as rods regulate P23H rhodopsin, with previous studies demonstrating that Rho P23H mRNA is degraded through mRNA decay and ribosome quality control, while translated P23H rhodopsin is degraded through ER-associated degradation (36,46). Another possibility is that mutant mRNA is subjected to miRNA-mediated decay, as previous studies have shown that miRNAs play a crucial role in photoreceptor homeostasis, function, and survival (47).…”
Section: Discussionmentioning
confidence: 97%